Innovation for Inclusive Growth: Towards a Theoretical Framework and a Research Agenda - GEORGE, Gerard (Institutional Knowledge at Singapore Management University, 2012)
Inclusive innovation, which we define as innovation that benefits the disenfranchised, is a process as well as a performance outcome. Consideration of inclusive innovation points to inequalities that may arise in the development and commercialization of innovations, and also acknowledges the inequalities that may occur as a result of value creation and capture. We outline opportunities for the development of theory and empirical research around this construct in the fields of entrepreneurship, strategy, and marketing. We aim for a synthesis in views of inclusive innovation and call for future research that deals directly with value creation and the distributional consequences of innovation.